Peran Kritis Advokat dan Organisasi Profesi Advokat dalam Sistem Peradilan Mengenai Tantangan dan Peluang di Era Modern - Samsi, Sofia Nur Azizah; Subrata, Rusli (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In a modern era filled with social dynamics, technology, and legal changes, the role of Advocates and Advocacy Organizations in the justice system has become increasingly critical. To explore the challenges and opportunities faced by Advocates and Advocate Professional Organizations in the context of the modern era, as well as how they can play a critical role in facing these challenges. This research method uses a qualitative research method with an empirical juridical method approach. The results showed that the main challenge faced by Advocates and Advocate Professional Organizations is adaptation to technological advances that continue to grow. The digital era brings major changes in the way Advocates and Advocate Professional Organizations conduct document data collection, obtain evidence, and interact with clients and other parties in the justice system. In addition, social, political, and economic changes also affect the dynamics of legal practice, introducing new complexities in the resolution of legal disputes. However, amidst these challenges, the modern era also brings opportunities for Advocates and Advocate Professional Organizations. The integration of technology in the practice of law enables Advocates and Advocacy Organizations to improve the efficiency and accessibility of the justice system. In addition, Advocates and Advocacy Organizations have the opportunity to become agents of change in society by using their voices to fight for fairer and more inclusive legal reforms. With integrity, social sensitivity, and the use of technology, Advocates and Advocacy Organizations can shape the future of a better and fairer justice system in this modern era.